A new species of Asian gracile skink (Scincidae: Lygosominae: Subdoluseps) from the rain-shadow belts of Nilgiri hills, Western Ghats, India - Ganesh, S. R.; Srikanthan, Achyuthan N.; Ghosh, Avrajjal; Adhikari, Omkar Dilip; Kumar, Shree Varsha Vijay; Datta-Roy, Aniruddha (Zootaxa, 2021)
We describe a new species of Asian gracile skink from the dry leeward slopes of the Nilgiri hills, Tamil Nadu state, India which forms a part of the eastern, rain shadow escarpment of the Western Ghats in peninsular India. The new species, Subdoluseps nilgiriensis sp. nov., is characterized by: slender, small-sized body (47–67 mm); sandy brown above, with each scale tipped with black; a thick black lateral band from snout to tail; a distinct white labial streak; dirty white venter, with throat having mild black striations; 28–29 midbody scale rows; 71–74 mid ventral scales; 66–69 paravertebral scales. The new species is described based on external morphological characters, genetic data and geographical isolation. Based on two mitochondrial DNA genes, we show that the new species shares a sister relationship with Subdoluseps pruthi (Sharma, 1977) which is found in parts of the Eastern Ghats in peninsular India. The discovery of this new population raises two novel scenarios. Firstly, it renders the genus Subdoluseps evolutionarily polyphyletic with respect to the Indian species included in this genus. Secondly, it falsifies the notion that S. pruthi group skinks are restricted to the Eastern Ghats. Our results further indicate that the dry zone of peninsular India has unrealized skink diversity that needs to be further explored.